KARAKTERISTIK KECEPATAN DAN ARUS MOTOR DC TERHADAP VARIASI TORSI PADA SISTEM PASTEURISASI SUSU - Aldian Ferdiansyah Mahendra; Ponco Siwindarto; n/a Wijono (Jurnal Mahasiswa TEUB, 2022)
Continuous pasteurization system is a pasteurization system where the material goes to the pasteurization site and is pasteurized in a short time. Continuous pasteurization is widely used in industrial scale. In a continuous pasteurization system, a motor and pump system is needed to move milk from one process to another. One type of motor that can be used as a pump is a separate-excited DC motor. DC motors can provide large torque and are easy to control so that DC motors are often found in various applications such as pumps, conveyors, and others. In this study, a simulation will be carried out using MATLAB/SIMULINK r2017a to determine the characteristics of the separately-excited DC motor when given a change in the duty cycle of the armature voltage to the rotor speed and the armature current when given load torque variation and nominal load torque. It was found that at zero load and nominal load torque, speed of the motor is directly proportional to the increase in the duty cycle of the armature voltage. Meanwhile, when the motor is given a nominal torque load so that it rotates at the nominal speed and then the load is increased until it reaches 5 times th